-3(6x-4)+6x=-3(x+1)

Simple and best practice solution for -3(6x-4)+6x=-3(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(6x-4)+6x=-3(x+1) equation:



-3(6x-4)+6x=-3(x+1)
We move all terms to the left:
-3(6x-4)+6x-(-3(x+1))=0
We add all the numbers together, and all the variables
6x-3(6x-4)-(-3(x+1))=0
We multiply parentheses
6x-18x-(-3(x+1))+12=0
We calculate terms in parentheses: -(-3(x+1)), so:
-3(x+1)
We multiply parentheses
-3x-3
Back to the equation:
-(-3x-3)
We add all the numbers together, and all the variables
-12x-(-3x-3)+12=0
We get rid of parentheses
-12x+3x+3+12=0
We add all the numbers together, and all the variables
-9x+15=0
We move all terms containing x to the left, all other terms to the right
-9x=-15
x=-15/-9
x=1+2/3

See similar equations:

| -2/5×y=4 | | 7a+5=47 | | -6(y-7)=-5y-5 | | 5x-45=x+15 | | 3(x+12-5)x=22 | | 7(w-1)-9=-2(-9w+9)-7w | | P(n)=0.8n+5.50 | | 14=7m/8 | | -5x-5(7x+16)=240 | | (x)=-4+10 | | 19w-13-6w=85 | | (A)x15=45 | | (n)=0.8n+5.50 | | s/4+3=15 | | t-8=42 | | -30=-8w+6(w-8) | | 7p-5=6p+28 | | 8x+4=15x-9 | | .875x=14 | | -2(u+4)=4u-8+2(3u+7) | | 1/3+2/3m=m-2/3 | | 2.6=8.2+y | | 7÷8x=14 | | 2/5x-9=-1 | | (6=x)+4+4Y-9=180 | | 1.34x-0.334=x+7 | | 12k-3(k+5=48 | | 7(8-3x)=-91 | | (14.3-2.5)/4=x | | -10+5=7b=5 | | 3+1=c+1 | | −2(−3x+3)+3x+3=78 |

Equations solver categories